Rapid hydrothermal synthesis of mesoporous NiS2 and NiSe2 nanostructures for wastewater treatment - Mohammad Abbas Lone; Vipin Shrotriya; Tanweer Ahmad Lone; Thamraa Alshahrani; Md Amzad Hossain; Mohamed Adam; M Burhanuz Zaman (Heliyon, 2023)
In the present study, single phase nickel based disulphide (NiS2) and diselenide (NiSe2) nanostructures were prepared hydrothermally in a short time span (4 h) under subcritical temperature (160 °C). The nanostructures grow in cubic crystal phases. Average crystallite sizes and intrinsic microstrains were determined using Williamson–Hall (W–H) plot analysis. Hollow NiS2 nanospheres and bipyramidal NiSe2 nanostructures are reported that are suitable for surface related applications. Thermal gravimetric analysis (TGA) indicated high stability of the nanostructures at elevated temperatures. Optical studies indicated visible light activeness of the nanostructures exhibiting sharp band edges. The nanostructures are mesoporous in nature with NiS2 and NiSe2 having respectively a large specific surface area of 310 m2/g and 177 m2/g. A primarily work done to determine the electrochemical nature of the nanostructures showed the materials are pseudo-capacitive in nature with specific capacitances of 1022 F/g and 480 F/g respectively for NiS2 and NiSe2. The photo-catalytic activity of the nanostructures was explored against a colourless pollutant; phenol. The nanostructures degraded most of the phenol (>90 %) under visible light illumination and the reusability experiments performed determined industrial value of the photocatalysts.